Second-Generation P-Values, Shrinkage, and Regularized Models - Stewart, Thomas G.; Blume, Jeffrey D. (Frontiers in Ecology and Evolution, 2019)
Second-generation p-values (SGPVs) are a novel and intuitive extension of classical p-values that better summarize the degree to which data support scientific hypotheses. SGPVs measure the overlap between an uncertainty interval for the parameter of interest and an interval null hypothesis that represents the set of null and practically null hypotheses. Although SGPVs are always in the unit interval, they are not formal probabilities. Rather, SGPVs are summary measures of when the data are compatible with null hypotheses (SGPV=1), compatible with alternative hypotheses (SGPV=0), or inconclusive (0<SGPV<1). Because second-generation p-values differentiate between inconclusive and null results, their Type I Error rate converges to zero along with the Type II Error rate. The SGPV approach is also inferentially agnostic: it can be applied to any uncertainty interval about a parameter of interest such as confidence intervals, likelihood support intervals, and Bayesian highest posterior density intervals. This paper revisits the motivation for using SGPVs and explores their long-run behavior under regularized models that provide shrinkage on point estimates. While shrinkage often results in a more desirable bias-variance trade-off, the impact of shrinkage on the error rates of SGPVs is not well understood. Through extensive simulations, we find that SPGVs based on shrunken estimates retain the desirable error rate behavior of SGPVs that we observe in classical models - albeit with a minor loss of power – while also retaining the benefits of bias-variance tradeoff.